Supporting teachers to lead invention education with high school students - Audra Skukauskaite; Stephanie Renee Couch (Quality Education for All)
Purpose – The purpose of this study was to examine ways high school educators new to invention education (IvE) pedagogy can develop confidence in their ability to facilitate high school students’ work as part of this transdisciplinary (STEM+) problem-based approach to teaching. Design/methodology/approach – This focused ethnographic study traced participants’ interactions across a three-day event that included professional development for 36 educators. The authors documented the discourse, actions and broader social context in which the interactions took place between the educators and others. Ethnographic fieldnotes, interview transcripts and pre- post-experience surveys were analyzed to determine ways the professional development opportunities shaped the educators’ perspectives on their confidence to facilitate IvE with their students. Findings – Many different types of learning opportunities were afforded across the three days, including lectures by professor-inventors, seminars, talks with experienced educators, hands-on activities and engagement with high school students. The 36 educators indicated they were more confident in their ability to lead invention projects (55% more confident, 41% much more confident) due to participation. Originality/value – IvE is an emerging form of problem-based learning in which educators engage learners in the identification of problems and the design and development of new, novel, useful and unique technological solutions (i.e. inventions) that help people. The study responds to the need for research on ways educators learn how to take-up IvE pedagogy.